Experimental study on cooling of mobile phone with PCM - Ng, Joel Weixiong. (2013)
As smartphones continue to develop at an alarming rate, the technology that complements them improves speedily as well. From the Iphone to the Samsung smartphones, producers are compacting as much software and hardware as they can into a pocket-sized mobile without compromising on quality. As such, these phones are not only getting slimmer, they are getting more powerful as well. And because of this, more heat is generated within the smartphone itself. Thus, something must be done to control this heat and prevent it from causing any discomfort to the user.